Analisis Strategi Bisnis Bank Digital Syariah di Indonesia - Handayani, Disfa Lidian; Anisa, Widiya Nur (AL-Muqayyad, 2023)
Digital banks are part of the digitalization of financial institutions which aims to facilitate financial inclusion for all groups. Sharia digital banks are a type of banking institution that provides practical and easy online services based on sharia principles so that customers do not need to come to a branch office. Sharia digital banks are among the latest innovations in the banking industry in Indonesia. This article aims to analyze the internal and external conditions of Islamic digital banks in Indonesia and formulate strategies that will be implemented by Islamic digital banks to take advantage of strengths and opportunities and overcome weaknesses and threats. This research uses the SWOT method. The results show several strengths (such as being the first pure digital Islamic bank in Indonesia, recipient of the Most Promising Islamic Digital Bank 2021 award at the CNBN Indonesia Award 2021), weaknesses (such as requiring a supporting internet connection), opportunities (such as: continued growth of internet users in Indonesia), and threats (such as cybercrime attacks). Based on the results of the SWOT analysis, the comparative advantage cell, mobilization cell, divestment/investment cell and damage control cell were obtained.